ChemInform Abstract: Pursuing Chemical Efficiency by Using Supported Organocatalysts for Asymmetric Reactions under Aqueous Conditions. Issue 45 (November 2015) - Guillena, Gabriela; Alonso, Diego; Baeza, Alejandro; Chinchilla, Rafael; Flores‐Ferrandiz, Jesus; Gomez‐Martinez, Melania; Trillo, Paz
Abstract Review: 171 refs.